2022
DOI: 10.3389/fcimb.2022.901590
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Role of Low-Density Neutrophils During Mycobacterium tuberculosis Infection

Abstract: Tuberculosis (TB) is caused by infection with the bacterium Mycobacterium tuberculosis (Mtb), which primarily infects the lungs but can also cause extrapulmonary disease. Both the disease outcome and the pathology of TB are driven by the immune response mounted by the host. Infection with Mtb elicits inflammatory host responses that are necessary to control infection, but can also cause extensive tissue damage when in excess, and thus must be precisely balanced. In particular, excessive recruitment of neutroph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 101 publications
(154 reference statements)
0
7
0
Order By: Relevance
“…We collected the BALF from patients with LTBI and TB and assessed cell composition and architecture using scRNA-seq. Data from three healthy control donors (HC) were downloaded from our public database [ 4 ] . The BALF from seven patients with TB was collected from the diseased regions of the lung and the lesion-offside normal lung tissues from three patients with TB (TBN).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We collected the BALF from patients with LTBI and TB and assessed cell composition and architecture using scRNA-seq. Data from three healthy control donors (HC) were downloaded from our public database [ 4 ] . The BALF from seven patients with TB was collected from the diseased regions of the lung and the lesion-offside normal lung tissues from three patients with TB (TBN).…”
Section: Resultsmentioning
confidence: 99%
“…However, it is extremely difficult to obtain lung tissue samples from Mtb-infected populations, particularly those with LTBI. Several previous studies have used animal models, including monkeys and mice, to simulate human immune responses against Mtb infection [ 3 , 4 ]. However, owing to the differences in the immune responses of certain species, the latent infection state in animal models remains controversial.…”
Section: Introductionmentioning
confidence: 99%
“…The existence of distinct neutrophil subsets or temporary functional states has been demonstrated in several species [ 62 ], including naïve cattle [ 63 ]. Some subsets have demonstrated an increased phagocytic activity [ 64 ] and, in active tuberculosis, low density neutrophils are present in high numbers, but its role is still unknown [ 65 ], these recent findings show that the available information about neutrophils and their role in mycobacterial diseases is scarce. Regarding neutrophil degranulation in response to Map , it was clearly directional, with MPO + granules observed mostly over bacterial clumps.…”
Section: Discussionmentioning
confidence: 99%
“…A recent report characterizing the susceptibility of mice deficient in Nos2 found that GR1 int granulocytes were long-lived, unable to control bacterial growth, and were not suppressive even with increased IL10 production (33). In humans, low density granulocyte populations are associated with severe susceptibility to TB and may be analogous to these permissive GR1 int cells seen in susceptible mice (37). It is possible that these granulocytes are not directly driving the susceptibility but rather are associated with uncontrolled TB disease caused by other defects in the host response.…”
Section: Discussionmentioning
confidence: 99%